Technical methods in the works of plastic artists of the sixties and their employment in the productions of students of the Department of Art Education (Journal of the College of Basic Education, 2022)
The plastic arts witnessed transformations in the aesthetic manifestation through the possibilities of technical methods, by using a range of means and methods, according to the needs of art in experimentation with the aim of translating the ideas of the artist. ) New technologies such as collage, tracing, composition, assembly and other techniques,